Rancang Bangun Sistem Peringatan Dini Bencana Banjir Di Kabupaten Madiun Berbasis Website Dan SMS Gateway Menggunakan Mikrokontroller Arduino - Halillur Nur Afandi; Landung Sudarmana; Dayat Subekti; Nafisa Alfi Sa'diya (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Madiun Regency is one of the districts on the island of Java, precisely in the province of East Java. Based on research from the Center for Volcanology and Geological Disaster Mitigation (PVMBG), Madiun City has several potential disasters, one of which is flooding with a high category. This is because Madiun Regency has two streams, namely Kali Sono and Kali Piring which head up on the slopes of Mount Wilis, Madiun Regency. Both times it ended in the Jerohan River in the Balerejo District, Madiun Regency which is a tributary of the Bengawan Madiun River. When heavy rains fell, parts of Madiun City were immediately inundated by flood waters. To anticipate floods, this research proposes a prototype design of a flood disaster early warning system using multiple sensors based on the Global System for Mobile Communications (GSM) in Madiun Regency. Which in the design uses the waterfall and Arduino methods. The prototype built is able to provide early warning information. The data that has been taken can be displayed on the web which functions as a monitoring system, so that officers can carry out supervision more easily and take action when the situation is dangerous. With the prototype and the system made, it is expected to be able to minimize losses caused by floods.